THE VIRTUAL LEARNING BASED ON CHARACTER EDUCATION IN ARABIC SUBJECTS - Ana Durrotul Hikmah; Siti Henik Luluk Badriyah; Ahmad Ridwan (Program Studi Pendidikan Bahasa Arab, 2023)
During the Covid-19 pandemic, the internalization of character education values ​​in Arabic Education instruction was forced to adapt and undergo various changes, both planning, design, implementation to assessment, and the shifting of the functions of teachers and parents. This article aims to find out the implementation of character education in Arabic Education during the Covid 19 pandemic at elementary schools. The research was conducted at MTs Aswaja Ngunut, Tulungagung. This research was a qualitative descriptive approach. The data collection method done with depth interview, participant observation, and documentation. The results of this research showed that the character education of students in Arabic Education instruction was carried out online using the Zoom Meet platform and WhatsApp group. The religious character is instilled by praying together before and after learning, practicing Dhuha prayer at home, online tadarus together, and instilling the values ​​of tolerance in learning. The students are given independent or group assignments to instill an attitude of independence and cooperation. The teacher instilled the importance of the characteristics of the Prophet such as shiddiq, tabligh, amanah, and fathonah to instill integrity. And students are also taught how to love culture and the homeland as a form of nationalism. Arabic Education teachers and parents collaborate and strengthen each other's roles in supporting the strengthening of character education values ​​as long as students carry out learning from home.